Pelatihan dan Pendampingan Pemanfaatan Daur Ulang Botol Plastik Menjadi Karya Seni Pada Lansia di Panti Rumah Bahagia Bintan - Rendana, Agung; Yunita , Rama; Turisna , Reni; Fospawati , Rinuke (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Garbage is a very difficult problem to overcome, especially in developing countries. Even though it can be overcome, the costs required for processing this waste are generally relatively large, especially when using high technology. Nowadays, the waste that we encounter is plastic waste because so many people use plastic in carrying out their daily activities. Now we know that used plastic bottles have many benefits. So, from now on, don't ever abandon used plastic bottles; instead of throwing them away, we'd better make them into more useful items. Besides, there's nothing wrong with making crafts to fill our free time. We can make unique crafts, and what's more, if the results are good, we can sell these unique items.